2017
DOI: 10.1039/c7ob01697b
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical generation and trapping of 3-oxacyclohexyne

Abstract: The strained heterocyclic alkyne, 3-oxacyclohexyne, was generated photochemically for the first time using a cyclopropanated phenanthrene precursor, and trapped by cyclopentadienones as Diels-Alder adducts. The precursor initially produced the putative 3-oxacyclopentylidenecarbene that subsequently rearranged to the cycloalkyne. Computational studies indicate that the carbene favors a singlet state, and the barrier for its ring expansion by a 1,2-shift of the carbon proximal to oxygen is lower in energy than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…This is comparable to the ΔE ST of ∼41 kcal mol −1 that we previously reported (B3LYP/6-31+G*). 57 We also reported similar energy gaps (ΔE ST ) of 39.6 and 40.3 kcal mol −1 for cyclobutylidene (9a) and cyclopentylidene (9b), respectively, at the B3LYP/6-31+G* level of theory (Scheme 4c). 56 Moreover, alkylidenecarbenes are generally known to have singlet ground states.…”
Section: ■ Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…This is comparable to the ΔE ST of ∼41 kcal mol −1 that we previously reported (B3LYP/6-31+G*). 57 We also reported similar energy gaps (ΔE ST ) of 39.6 and 40.3 kcal mol −1 for cyclobutylidene (9a) and cyclopentylidene (9b), respectively, at the B3LYP/6-31+G* level of theory (Scheme 4c). 56 Moreover, alkylidenecarbenes are generally known to have singlet ground states.…”
Section: ■ Introductionsupporting
confidence: 58%
“…56 In an analogous manner, we demonstrated the extension of this strategy to access a strained heterocyclic alkyne by photolyzing 11 to form 3-oxacyclopentylidenecarbene 12, which then rearranges to 3-oxacyclohexyne (13) (Scheme 2). 57 Herein, we report the use of femtosecond time-resolved absorption (fs-TA) spectroscopy to directly observe, for the first time, the ylide formed by the interaction of an alkylidenecarbene (12) with acetonitrile and measure its lifetime. The experimental outcome is consistent with results from density functional theory (DFT) calculations which indicate that ylide formation between 12 and acetonitrile is a significantly more favorable process compared to the ring expansion in 12.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another distinctive feature of 13 is that its triple bond is significantly elongated with a calculated length of 1.28 Å. This value is intermediate between the length of a C=C bond in cyclopentene (~1.32 Å) [51] and our calculated value for the C≡C bond (1.22 Å) in cyclopentyne [15]. Thus, 13 appears to display a partial triple bond, rather than a formal one, in order to alleviate ring strain.…”
Section: Resultsmentioning
confidence: 65%
“…By extending this method to cyclic alkylidenecarbenes ( 4 ) and carbenoids ( 5 ), in which the formally sp 2 -hybridized carbon connected to the carbene center is part of a ring, strained cycloalkynes ( 6 ) have also been generated (Scheme 1b) [4,7,8,9]. In recent years, our laboratory has reported that cyclopropanated phenanthrene systems such as 7 [10,11,12,13] and 8 [14,15] can serve as photochemical precursors to 1 and 4 respectively (Scheme 2), and thus provide light-induced routes to the corresponding linear and cyclic alkynes.…”
Section: Introductionmentioning
confidence: 99%